2016
DOI: 10.21577/0103-5053.20160311
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Influence of Biodiesel in Soot Emissions of Diesel Laminar Diffusion Flames

Abstract: In this work the presence of soot in laminar diffusion of diesel and blends diesel/biodiesel flames were investigated in the following proportions: 5, 10, 20 and 50% of biodiesel. The technique of laser-induced incandescence (LII) was used for the soot detection. Horizontal mapping were performed at two heights (80 and 260 mm above the burner) to investigate the distribution of soot along the studied flames. The experiment was performed with a pulsed Nd:YAG laser with the wavelength of 1064 nm. The results hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…During this process, the amount of electricity, diesel, steel (used equipment), and copper (electric motors) was investigated. The indirect release of environmental pollutants caused by these inputs was estimated using EcoInvent international databases available in SimaPro 8.1 software [32], and the direct release of pollutants from the workforce was calculated using the method developed by (Nguyen and Hermansen [41].…”
Section: Inventorying In the Ginning And Oiling Stagementioning
confidence: 99%
See 1 more Smart Citation
“…During this process, the amount of electricity, diesel, steel (used equipment), and copper (electric motors) was investigated. The indirect release of environmental pollutants caused by these inputs was estimated using EcoInvent international databases available in SimaPro 8.1 software [32], and the direct release of pollutants from the workforce was calculated using the method developed by (Nguyen and Hermansen [41].…”
Section: Inventorying In the Ginning And Oiling Stagementioning
confidence: 99%
“…The results posited that the total amount of carbon dioxide gas absorbed during the entire biological life cycle of rapeseed biodiesel is much greater than its emission, and biodiesel produced from rapeseed is an environmentally compatible energy source. The results of studies performed by Kumar Agarwal et al [3] and Tolomelli Luiz et al [32] showed that the use of diesel fuel and its combustion in the engine create large amounts of PM 2.5 particles suspended in the air. Examining different studies shows that there is no comprehensive research on the biodiesel production process cycle from different sources (different oils).…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, these emission standards do not concern an additional compounds or chemical elements contained in the exhaust emissions or exhaust vapour [10], PM, [11], black carbon/carbon black (BC/CB) [12], or in the soot [13], formed by the diesel or biodiesel [14], from combustion engines [15]. Nevertheless, chemical elements adsorbed by carbonous particles present significant volumetric as well as mass fraction of the total Diesel Particulate Matter (DPM) or soot emission contents.…”
Section: Introductionmentioning
confidence: 99%